التعدّدية الحزبية في أنظمة الحكم السياسية النيابية دراسة بين المظاهر والتأثير - الكيلاني سعيد عمار محمد (Sharwes Scientific Journal, 2024)
Western political systems of government with representative and presidential political systems are characterized by bipartisanship despite the different style of governance in them, and this puts us in front of the following questions: What is the philosophy of bipartisanship in Western political thought? What are the manifestations and forms of bipartisanship in Western political systems? What are the effects of bipartisanship on representative political systems? What are the manifestations and features of multiparty in representative political systems? This study aims to identify the philosophy of bipartisanship in Western political thought, clarify the manifestations and forms of bipartisanship in Western political systems, and explain the effects of bipartisanship on the parliamentary political system, and reveal the manifestations and features of multiparty in parliamentary political systems, the researcher has followed in this study the descriptive approach to describe and interpret the phenomenon of bipartisanship, and the researcher also used the approach